Tales of Horror - Stocker, Bram (Heinimann Publishers (Oxford) Ltd, 1983)
This book comprises of three strange and frightening short stories by the author of Dracula: The Judge's House, The Iron Maiden and The Return of Abel Behena.
Keywords: Scary